The development and validation of an emotional vulnerability scale for university students - Yamaguchi, Shinji; Kawata, Yujiro; Murofushi, Yuka; Ota, Tsuneyoshi (Frontiers in Psychology, 2022)
This study developed an emotional vulnerability scale and examined its reliability and validity with a sample of university students. In health psychology, a measurement of emotional pain (“hurt feelings”) can contribute to the prevention and improvement of physical and mental health problems in daily life. We collected data from 361 Japanese university students (186 men and 175 women; mean age = 19.6 ± 0.98 years). From preliminary interviews with 20 participants, 42 semantic units were extracted. For scale development, a questionnaire survey was conducted using the 42 extracted categories, and exploratory and confirmatory factor analyses were performed. Four factors (16 items) emerged, which were both reliable and valid: 1) “vulnerability toward criticism or denial,” 2) “vulnerability toward worsening relationships,” 3) “vulnerability toward interpersonal discord,” and 4) “vulnerability toward procrastination and emotional avoidance.” This scale can be useful to understand vulnerability in everyday situations and grasp the vulnerable conditions experienced by individuals. This can help prevent stress responses (such as depression and sadness) and mental health problems, which are valuable contributions to health psychology.